Awareness and Perception on the Use of Open Educational Resources Among Public Senior High School Teachers - Guzman, Frances Aleyanna D.; Francisco, Zian Mark P.; Azurin, Aster Gabriel L.; Lapuz, Eunice Keith P.; Magtoto, Christoper Kyle L.; Vergara, Charles Nicolo C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Education plays an essential role in shaping not only one’s knowledge but also in addressing global issues. However, the limited availability of learning resources in the Philippines continues to hinder the delivery of quality education. This suggests that Open Educational Resources (OER) can be a solution by providing free and adaptable materials that can enhance teaching. However, few studies in the Philippines have examined how senior high school faculty perceive and adopt OER, particularly in regional contexts. Thus, this research explores public senior high school teachers' awareness and perception of using OER. Using convenience sampling, the study polled 82 public senior high school instructors through a quantitative-descriptive research approach. Results indicate that most of the faculty are moderately to highly familiar with OER and have an overall positive perception of it. However, concerns persist regarding usability issues, preparation time, and institutional support. The research underlines the importance of focused training initiatives and policies in institutions to encourage teachers to adopt OER further.